2015
DOI: 10.1007/s10450-015-9697-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of bio-organoclays using nonionic surfactant

Abstract: The present study was aimed at the preparation and characterization of tailor made hybrid materials, whose peculiar hosting capability could be exploited in biotechnological applications. With this purpose, the modification of K10 montmorillonite by intercalation of Tween 20 surfactant, was accomplished. The influence of two internal parameters, namely pH and surfactant/clay ratio, on the surfactant uptake ability by clay was investigated. The adsorption mechanism was elucidated on the basis of complementary k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…It is worth to underline that the different behavior of metal and dye is in accordance with the results of the adsorption isotherms and it corroborates the hypothesis that the dye adsorbs onto Mt Perusal of diffractograms evidences the presence of the peaks characteristic of the hydrated montmorillonite k10 clay, i.e., one at 2θ approximately equal to 8.9 • (peak 1) which corresponds to the basal interlayer, and a reflection peak at a lower 2θ value (~6 • ) (peak 2), which, according to literature [74,[126][127][128][129][130], is attributed to the majority of the interlayer spaces being intercalated with water molecules as proved by the disappearance of this refection peak after dehydration processes [129].…”
Section: Xrd Characterizationsupporting
confidence: 89%
“…It is worth to underline that the different behavior of metal and dye is in accordance with the results of the adsorption isotherms and it corroborates the hypothesis that the dye adsorbs onto Mt Perusal of diffractograms evidences the presence of the peaks characteristic of the hydrated montmorillonite k10 clay, i.e., one at 2θ approximately equal to 8.9 • (peak 1) which corresponds to the basal interlayer, and a reflection peak at a lower 2θ value (~6 • ) (peak 2), which, according to literature [74,[126][127][128][129][130], is attributed to the majority of the interlayer spaces being intercalated with water molecules as proved by the disappearance of this refection peak after dehydration processes [129].…”
Section: Xrd Characterizationsupporting
confidence: 89%
“…The (001) reflection shifted to a lower diffraction angle for MSH particles as compared to untreated montmorillonite, which implied an increased interlayer distance from 14.9 to 18.0 Å. This 3.1 Å increase agrees well with previous studies (Calabrese et al, 2016;Calabrese et al, 2017). Under the assumption that the thickness of an individual montmorillonite layer is 10 Å (Ploehn and Liu, 2006), the resulting distance between individual montmorillonite layers was 8 Å, corresponding to 5-6 C-C alkane bonds (Skinner, 1945).…”
Section: Polysorbate 20 Is Intercalated In Msh Particlessupporting
confidence: 88%
“…Calabrese and co-workers have successfully incorporated polysorbate 20 in montmorillonite to obtain delayed release of cinnamic acid (Calabrese et al, 2016;Calabrese et al, 2017), and they showed that 5 polysorbate 20 facilitated the release of cinnamic acid from montmorillonite. Their studies also confirm the strong interactions between montmorillonite and polymers or surfactants that contain oxyethylene groups (-CH2-CH2-O-), like polysorbate (Aranda and Ruiz-Hitzky, 1992).…”
mentioning
confidence: 99%
“…In the blank Mt case, the 001 reflection was observed at 2θ = 5.37°( d = 16.5 Å). According to the literature (Bromberg et al, 2011;Cui et al, 2008;Calabrese et al, 2016;Bertolino et al, 2016) this reflection has been ascribed to the Mt with interlayer spaces filled with hydrated cations.…”
Section: Xrd Characterizationmentioning
confidence: 90%